Implementation of Religious Moderation Values in Early Childhood (Research at Joy Kids Kindergarten Tawang District Tasikmalaya City West Java) - Rizal, Soni Samsu (Journal of Gemilang, 2024)
This study aims to examine the implementation of religious moderation values ​​in early childhood at Joy Kids Kindergarten, Tawang District, Tasikmalaya City, West Java. The research method used is a qualitative approach with a case study, which allows for an in-depth understanding of the process, meaning, and context of implementing religious moderation in an early childhood education environment. The subjects of the study included teachers, principals, and parents of students who were selected purposively based on their direct involvement in the learning process and management of character values ​​in schools. Data collection techniques were carried out through participatory observation, documentation studies, and interviews to obtain a comprehensive picture of learning strategies, social interactions, and school culture that support the internalization of moderation values. The results of the study showed that the implementation of religious and socio-emotional moderation values ​​in early childhood was effective with a play approach that was in accordance with the child's developmental stage (developmentally appropriate). The golden period of social imitation was utilized optimally, where teachers and peers acted as role models in instilling attitudes of tolerance, empathy, and anti-violence. The role of teachers as active facilitators and examples of polite language are key factors in the success of moderation learning, although further training is still needed so that the application of moderation values ​​is not merely symbolic. In addition, the aspect of acceptance of religious traditions and rituals needs to be strengthened so that children can appreciate diversity more deeply. Thus, Joy Kids Kindergarten has succeeded in creating an inclusive and harmonious learning environment, but it still needs to develop a program to strengthen traditions and increase teacher capacity so that moderation values ​​can be embedded comprehensively in children's characters.